Preparasi dan Karakteristik Arang Aktif dari Sekam Padi dengan Aktivator Naoh sebagai Adsorben Metilen Biru - Ni Kadek Ayu Candra Dharmayanti; I Made Siaka; I Wayan Sudiarta (Jurnal Kendali Teknik dan Sains, 2025)
Rice husk is a waste originating from agricultural waste that has not been utilized properly. The purpose of this study was to compare NaOH-activated rice husk activated charcoal with unactivated activated charcoal, and to measure the adsorption capacity of activated charcoal to methylene blue. Gravimetry, volumetry, and spectrophotometry are the analytical techniques used in this analysis. In this study, 1.5 M rice husk activated charcoal with NaOH showed the best results. It showed a water content of 8.81%, ash content of 5.87%, volatile matter content of 6.60%, and carbon content of 78.72%. In addition, the results showed that NaOH-activated rice husk activated charcoal has characteristic capabilities and adsorption capacity to methylene blue that meets SNI. The longer it is reasonable, the more rice husk activated charcoal.